Follow-up Results of Endovascular Aneurysm Repair Following Abdominal Visceral Debranching - Didem Melis Oztas (Brazilian Journal of Cardiovascular Surgery, 2022)
ABSTRACT Introduction: The aim of this study is to present a series of six cases with thoracoabdominal aneurysm treated with hybrid technique in our center. Methods: Between May 2015 and December 2018, the data of six patients with thoracoabdominal aneurysms and various comorbidities who underwent visceral debranching followed by endovascular aortic aneurysm repair were reviewed retrospectively. Results: Patients’ mean age was 65.3±19.6 years. All of them were male. Comorbidities were old age, congestive heart failure, coronary artery disease, chronic obstructive pulmonary disease, previous surgical interventions, and/or esophageal hemangioma. Except for one patient who underwent coronary artery bypass grafting (inflow was taken from ascending aorta), debranching was performed from the right iliac artery. Debranching of four visceral arteries (superior mesenteric artery, celiac trunk, and bilateral renal right arteries) was performed in three patients, of three visceral arteries (superior mesenteric artery, celiac trunk, right renal artery) was performed in one, and of two visceral arteries (superior mesenteric artery, celiac trunk) was performed in two patients. Great saphenous vein and 6-mm polytetrafluoroethylene grafts were used in one and five patients, respectively, for debranching. Endovascular aneurysm repair was performed following debranching procedures as soon as the patients were stabilized. In total, three patients died at the early, mid, and long-term follow-up due to multiorgan failure, pneumonia, and unknown reasons. Conclusion: Hybrid repair of thoracoabdominal aneurysms may be an alternative to fenestrated or branched endovascular stent grafts in patients with increased risk factors for open surgical thoracoabdominal aneurysm repair; however, the procedure requires experience and care.